2015
DOI: 10.1186/s12889-015-2038-1
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to cooking fuels and birth weight in Lanzhou, China: a birth cohort study

Abstract: BackgroundEarly studies have suggested that biomass cooking fuels were associated with increased risk of low birth weight (LBW). However it is unclear if this reduced birth weight was due to prematurity or intrauterine growth restriction (IUGR).MethodsIn order to understand the relationship between various cooking fuels and risk of LBW and small for gestational age (SGA), we analyzed data from a birth cohort study conducted in Lanzhou, China which included 9,895 singleton live births.ResultsCompared to mothers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 39 publications
5
36
1
6
Order By: Relevance
“…A similar association has been found in several other studies conducted in developing countries such as Guatemala, India, Pakistan, China, and Zimbabwe. [26][27][28] Pregnant women in Bangladesh, like other developing countries, are not exempted from cooking regularly and are exposed to highly pollutant carbon dioxide (CO 2 ) and carbon monoxide (CO) laden air for a prolonged period of time. 29, 30 This is a concern as polluted air may hamper the required transplacental oxygen supply to the fetus and can cause intrauterine growth retardation (IUGR) of varying degrees and types.…”
Section: Discussionmentioning
confidence: 99%
“…A similar association has been found in several other studies conducted in developing countries such as Guatemala, India, Pakistan, China, and Zimbabwe. [26][27][28] Pregnant women in Bangladesh, like other developing countries, are not exempted from cooking regularly and are exposed to highly pollutant carbon dioxide (CO 2 ) and carbon monoxide (CO) laden air for a prolonged period of time. 29, 30 This is a concern as polluted air may hamper the required transplacental oxygen supply to the fetus and can cause intrauterine growth retardation (IUGR) of varying degrees and types.…”
Section: Discussionmentioning
confidence: 99%
“…*Estimated total deliveries per year in each hospital are according to the year 2015, before the study protocol was published 22L&D, labour and delivery room; NICU, neonatal intensive care unit; OT, operation theatre; SNCU, sick newborn care unit.…”
Section: Methodsmentioning
confidence: 99%
“…*Estimated total deliveries per year in each hospital are according to the year 2015, before the study protocol was published 22…”
Section: Methodsmentioning
confidence: 99%
“…Global estimate indicated that approximately 21 million infants are born with low birth weight each year. The incidence of low birth weight varies significantly across countries, ranging from 6 to 18% [6].…”
Section: Introductionmentioning
confidence: 99%